PENILAIAN KINERJA SISTEM IRIGASI DAERAH IRIGASI HULUDUPITANGO LIMBOTO DENGAN APLIKASI e-PAKSI - Djakaria, Mohamad Zulkarnain; Mohamad Januar Fuad; Nona Fitriana Madjowa (Universitas Bina Taruna Gorontalo, 2025)
This study aims to identify and evaluate the performance of the irrigation system in the Huludupitango Irrigation Area located in Limboto District, Gorontalo Regency. This area serves 1,054 hectares of agricultural land and plays an important role in supporting local agricultural productivity. However, with the increasing intensity of utilization, the performance of the irrigation system has declined due to insufficient attention to the maintenance of infrastructure and facilities. This study employs the e-PAKSI method (electronic–Asset Management and Irrigation System Performance), an internet-based system for comprehensively evaluating and managing irrigation assets. Based on the evaluation results, the performance score for physical infrastructure such as main structures reached only 9.41%, while the score for distribution channels was 11.19%, with an overall total score of 20.6%. These figures indicate that the irrigation system is in poor condition and requires attention and a comprehensive maintenance program from the government.